2022
DOI: 10.3390/molecules27175440
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbit[7]uril Complexation of Near-Infrared Fluorescent Azobenzene-Cyanine Conjugates

Abstract: Two new azobenzene heptamethine cyanine conjugates exist as dispersed monomeric molecules in methanol solution and exhibit near-infrared (NIR) cyanine absorption and fluorescence. Both conjugates form non-emissive cyanine H-aggregates in water, but the addition of cucurbit[7]uril (CB7) induces dye deaggregation and a large increase in cyanine NIR fluorescence emission intensity. CB7 encapsulates the protonated azonium tautomer of the 4-(N,N-dimethylamino)azobenzene component of each azobenzene–cyanine conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…The association constant for CB7 complexation of zwitterionic 1 in water or acidic media ( K a ∼ 10 6 M –1 ) was about 10 3 times higher than the binding of the free base form in an alkaline solution. This finding is consistent with the known propensity of cucurbiturils to complex guest molecules as their protonated forms. In 2022, we noted this supramolecular effect in a study that examined CB7 complexation of azobenzene-cyanine conjugates and found that CB7 encapsulated the 4-( N , N ′-dimethylamino)­azobenzene component of the conjugates as its protonated azonium tautomer to produce an absorption band at 534 nm . Interestingly, a separate study in 2022 by Sarruate and co-workers examined the complexation of compound 3 (4-aminoazobenzene) with CB7 and observed formation of a complex CB7@3·H + with an absorption band at 500 nm in acidic solutions (pH = 1, K a ∼ 10 5 M –1 ) .…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The association constant for CB7 complexation of zwitterionic 1 in water or acidic media ( K a ∼ 10 6 M –1 ) was about 10 3 times higher than the binding of the free base form in an alkaline solution. This finding is consistent with the known propensity of cucurbiturils to complex guest molecules as their protonated forms. In 2022, we noted this supramolecular effect in a study that examined CB7 complexation of azobenzene-cyanine conjugates and found that CB7 encapsulated the 4-( N , N ′-dimethylamino)­azobenzene component of the conjugates as its protonated azonium tautomer to produce an absorption band at 534 nm . Interestingly, a separate study in 2022 by Sarruate and co-workers examined the complexation of compound 3 (4-aminoazobenzene) with CB7 and observed formation of a complex CB7@3·H + with an absorption band at 500 nm in acidic solutions (pH = 1, K a ∼ 10 5 M –1 ) .…”
Section: Introductionsupporting
confidence: 73%
“…43−45 In 2022, we noted this supramolecular effect in a study that examined CB7 complexation of azobenzene-cyanine conjugates and found that CB7 encapsulated the 4-(N,N′dimethylamino)azobenzene component of the conjugates as its protonated azonium tautomer to produce an absorption band at 534 nm. 46 Interestingly, a separate study in 2022 by Sarruate and co-workers examined the complexation of compound 3 (4aminoazobenzene) with CB7 and observed formation of a complex CB7@3•H + with an absorption band at 500 nm in acidic solutions (pH = 1, K a ∼ 10 5 M −1 ). 31 A combination of experimental NMR data and computations led them to suggest that protonated 3 was encapsulated as an ammonium species in a cis azo conformation, but the report did not comment on the possibility of an azonium tautomer in a trans azo conformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Notably, no definitive evidence by far supports strong complexation between CB [7] and cyanine or hemicyanine dyes with cationic dimethylindolenium as the terminal heterocycle, which is unfortunate because of the general involvement of dimethylindolenium derivatives in near-infrared (NIR) fluorescence molecules. 24,25 In the present study, we report a "turn on" fluorescence probe to visualize the dimerization of μOR, which is the prime GPCR target for treatment of severe pain. 26 The sensing construct composed of CB [7] and a hemicyanine dye (HD) incorporated at the terminal position of aptamer strands for his-tags allows us to detect the dimerization process in intact living cells without the restricted requirement of singlemolecule microscopy (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 97%
“…Cucurbit­[ n ]­urils (CB­[ n ]­s, n = 5–8, 10, and 13–15), a family of macrocyclic homologues consisting of n glycoluril building blocks, have found a variety of uses in analytical and biomedical fields on account of their dynamic host–guest interactions to manipulate biomacromolecular assemblies of peptides, nucleic acids, and proteins. , In particular, the intricacy of CB­[ n ]-based recognition and the consequent modulation in the physical and spectral properties of the chromophoric guest molecules have become the spotlight in the development of supramolecular sensors. , A large body of work over the last 30 years has shown that CB[7], the most attractive homologue due to its high water solubility, forms robust intermolecular interaction with a variety of dye structures with the major groups involved being benzothiazolium, pyridinium, quinolinium, benzimidazole, coumarin, acridine orange, and several others in order to provide luminescent emission triggered by the confined space. Notably, no definitive evidence by far supports strong complexation between CB[7] and cyanine or hemicyanine dyes with cationic dimethylindolenium as the terminal heterocycle, which is unfortunate because of the general involvement of dimethylindolenium derivatives in near-infrared (NIR) fluorescence molecules. , …”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, researchers have developed indicator displacement assays (IDAs), , in which an optical guest (indicator) encapsulated by a macrocyclic molecule could be displaced from the host when exposed to appropriate competitive analytes, resulting in an optical change that can be observed by UV–vis or fluorescence spectroscopy. However, the development of suitable indicator dyes for γ-CD has remained a notable challenge due to its larger cavity size and associated weaker binding constants compared to those of β-CD . Indeed, dodecaborate clusters have been identified as one of the few classes of potential anchoring groups. ,, …”
mentioning
confidence: 99%